DISTANCE LEARNING DURING THE COVID-19 PANDEMIC: STRENGTHENING OF CHARACTER, PRODUCTIVITY, AND STEM COMPETENCY - Chaerul Rochman; Dindin Nasrudin; Rokayah Rokayah; Sri Rahayu; Catherien Suci Ramdhini Pertiwi; Ginanjar Ginanjar (JURNAL PENA SAINS, 2020)
This study aims to reveal the impact of distance learning during the Covid-19 pandemic on Science Technology Engineering and Math (STEM) competence, productivity, and students' character. This research uses mixed methods. The questionnaire instrument consists of STEM components, Learning Products, and character profiles obtained from Elementary School/Madrasah Ibtidaiyah, Junior High Schools, and Senior High Schools in Jakarta and Bandung. Furthermore, the data were analyzed, and it was concluded that the performance of all the variables studied had varying degrees. Besides, STEM literacy skills are closely related to learning productivity and character building of students at all levels of education. Therefore, distance learning after the Covid-19 pandemic needs to be planned well and considers the level of STEM literacy and character content clarity.